Analisis Hukum Internasional Tentang State Sponsored Terrorism - Corputty, Frandy Army; Wattimena, Josina Augustina Yvonne; Peilouw, Johanis Steny Franco (Faculty of Law, Universitas Pattimura, 2023)
Introduction: State is one of the subjects of international law that has the responsibility to protect the human rights of every individual within its sovereign territory. However, the facts show that there are countries that become sponsors or in other words the state provides support either directly or indirectly to terrorist groups to carry out their actions. This term is known as state sponsored terrorism which requires global attention considering that terrorism cases that occur often have links to the state.Purposes of the Research: 1. Review and discuss the regulation of State Sponsored Terrorism in International Law. 2. Review and discuss the implications for the enforcement of International Law.Methods of the Research: This study uses a normative juridical method with an analytical perspective using primary, secondary, and tertiary legal materials. This research technique is a literature study based on international legal regulations, scientific works and other literature related to state sponsored terrorism.Results of the Research: International law arrangements related to state sponsored terrorism still require special attention due to the large number of cases and indications of states being involved. Given that state sponsored terrorism is the root of various terrorism cases around the world. This shows that the international legal instruments that existed before the International Convention for the Suppression of the Financing Terrorism and United Nations Convention Against Transnational Organized Crime were considered unable to prevent and prohibit countries from sponsoring terrorists caused by the absence of the universal definition of terrorism. It is proven by international violations committed by sponsoring countries in order to fulfill their country's interests. State sponsored terrorism can also be considered as a problem for the protection of human rights. This can be seen when a sponsored terror act results in a violation of the right to life and the right to feel safe of every individual who is within the sovereign territory of the target country. The implication of state sponsored terrorism then causes overlapping jurisdictions between the International Court of Justice and the Security Council in enforcing international law so that the settlement of cases is still unclear.